Trends in clinical encounters and management for infertility among women attending Australian general practice: a national longitudinal study using MedicineInsight, 2011 to 2021 - Alice R Rumbold; Michael Davies; Danielle Mazza; Jacqueline Boyle; Vivienne Moore; Renae C Fernandez; Luke E Grzeskowiak (BMJ Open)
Objective To examine longitudinal trends in infertility management in women attending general practice.Design Cohort study using the national general practice dataset, MedicineInsight.Setting Australian general practice.Intervention(s) Not applicable.Participants The cohort included 2 552 339 women aged 18–49 years with one or more general practice clinical encounters between January 2011 and December 2021.Primary and secondary outcome measures(s) The primary outcome assessed was the proportion of women who had a clinical encounter related to infertility, stratified by year and age group. Second, the proportions of women receiving relevant clinical management actions, including selected pathology tests, imaging ordered and selected medications, were calculated. Univariable logistic regression analyses compared the likelihood of women having a documented clinical encounter related to infertility and receiving selected management actions based on individual characteristics. We also examined practice-level variation in the proportion receiving selected management for infertility by stratifying proportions based on practice site.Results A total of 2 552 339 women had one or more clinical encounters with their general practitioner (GP) between January 2011 and December 2021, of which 27 671 (1.1%) had a clinical encounter related to infertility management. The rate of infertility encounters increased from 3.4 per 1000 in 2011 to 5.7 per 1000 in 2021. Over episodes of care, half (50.9%) of women presenting for an infertility encounter had at least one specified pathology test, and almost a quarter (23.1%) had a specified imaging test. A relatively small proportion of infertility encounters (5.4%) resulted in prescribing of a selected infertility medication by the GP.Large variation in clinical management (pathology, imaging and medication prescribing) was evident according to both individual characteristics and also at the clinical-practice level. Factors associated with increased likelihood of being provided infertility medications included younger age, holding a Commonwealth concession card (indicating low income), lower socioeconomic status and living outside a major city.Conclusions Clinical encounters related to infertility are increasing in primary care, with large variation evident in corresponding clinical management. These findings support the development of clinical practice guidelines to enhance standardised and equitable approaches towards the management of infertility in primary care.